Menimbang Kebenaran: Paradigma Barat yang Berbasis Rasionalisme Vs. Islam yang Berbasis Wahyu - Ajmal Hadi Maulana; Alwan Hafidz Darmawan; Dhia Shabrina Shaheeb; Indra Hadi Kurniawan; Muhamad Parhan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the differences and similarities between the paradigm of Western rationalism, which places reason as the primary source of truth, and Islamic epistemology, which integrates revelation and reason in the pursuit of truth. The research employs a literature review method with a qualitative approach, drawing data from various scholarly works on Western and Islamic epistemological philosophy. A descriptive-comparative analysis is conducted to compare the fundamental concepts, methodologies, and implications of these two paradigms. The findings indicate that Western rationalism emphasizes reason and skepticism in verifying truth, with philosophers such as Descartes and Kant rejecting external authority in acquiring knowledge. Meanwhile, Islamic epistemology asserts that reason plays a crucial role but must align with revelation as the absolute source of truth. The study also finds that the dichotomy between revelation and reason is often misunderstood, whereas in Islam, they can complement each other. In conclusion, an integrative approach that combines the strengths of rationalism in scientific analysis with the moral and spiritual foundation of revelation can lead to a more comprehensive and applicable understanding in both knowledge and social life